2003
DOI: 10.1248/bpb.26.66
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Mechanism of Oleic Acid-Induced Percutaneous Penetration Enhancement: An Ultrastructural Study.

Abstract: The outermost layer of mammalian skin, the stratum corneum, by virtue of its unique architecture presents a significant barrier to the transdermal delivery of drugs. Recently, biophysical, morphological, and biochemical results have indicated that the stratum corneum forms a continuous sheath of protein-enriched corneocytes embedded in an intercellular matrix enriched in nonpolar lipids that are organized as lamellar layers.1,2) Although only 10 to 15% of the stratum corneum mass is comprised of lipids, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 17 publications
1
29
0
3
Order By: Relevance
“…The results showed that oleic acid might increase the epidermal per-meability via a mechanism involving perturbation of stratum corneum lipid bilayers and lacunae formation as penetration enhancing effects [74] . Butyl paraben, methyl paraben and caffeine were used as model penetrants to test the effects of unsaturated fatty acids in benzyl alcohol on percutaneous drug permeation.…”
Section: Fatty Acidsmentioning
confidence: 97%
“…The results showed that oleic acid might increase the epidermal per-meability via a mechanism involving perturbation of stratum corneum lipid bilayers and lacunae formation as penetration enhancing effects [74] . Butyl paraben, methyl paraben and caffeine were used as model penetrants to test the effects of unsaturated fatty acids in benzyl alcohol on percutaneous drug permeation.…”
Section: Fatty Acidsmentioning
confidence: 97%
“…The bent structure of the enhancer disrupts intercellular lipid packing, facilitating enhanced drug mobility. Disruption of lipid bilayers was also proposed by Jiang and Zhou [156] who used electron microscopy to examine structural alterations induced by oleic acid.…”
Section: Fatty Acidsmentioning
confidence: 97%
“…Oleic acid(OA), as an enhancer, has been widely used in the field of drug delivery [20][21][22] . It is a mono-unsaturated fatty acid and is Generally Recognized As Safe(GRAS) 23 .…”
Section: Introductionmentioning
confidence: 99%